1988
DOI: 10.1530/acta.0.1180495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a selenium deficient diet on thyroid function of normal and perchlorate treated rats

Abstract: Pregnant rats were submitted to a selenium\x=req-\ deficient diet immediately after mating; it was continued for 4 weeks after delivery. The pups were sacrificed at 3 and 4 weeks of age. Perchlorate, an antithyroid agent inhibiting iodide trapping in the thyroid, was administered via the drinking water to half of the rats. Rats submitted to a normal laboratory diet and to the experimental diet supplemented with selenium were used as controls. The effects of selenium deficiency were an increase in the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…Goldstein et al observed a decrease in PB 13"I after in vitro incubation of thyroid glands from selenium-deficient rats with 131I (27). Arthur et al (25) found a decrease in both T4 and T3 content in the thyroid gland from selenium-deficient rats, while Meinhold et al (28) found no change in T4 and T3 content in the thyroid from rats fed a selenium-deficient diet.…”
Section: Discussionmentioning
confidence: 99%
“…Goldstein et al observed a decrease in PB 13"I after in vitro incubation of thyroid glands from selenium-deficient rats with 131I (27). Arthur et al (25) found a decrease in both T4 and T3 content in the thyroid gland from selenium-deficient rats, while Meinhold et al (28) found no change in T4 and T3 content in the thyroid from rats fed a selenium-deficient diet.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate Se intake increases the efficiency of thyroid hormone synthesis [39]. This has been shown in animal studies, but not fully explained with respect to underlying mechanisms.…”
Section: The Hypothesis Of Thyroid Damage By Oxidative Stress During mentioning
confidence: 95%
“…To attain hypothyroidism, we employed an established protocol (van Hardeveld & Clausen 1984) in which rats were fed for 7 weeks an iodide-deficient diet with distilled water during the first 2 weeks and drinking water containing 144 mM KClO 4 for five consecutive weeks. This treatment has proven to result in the classic picture of hypothyroidism with decreased plasma T 4 and T 3 levels and rises in thyrotropin (TSH) (Golstein et al 1988, Yu et al 2002. Controls received the same diet, and drinking water to which 6·5 mg/l KI was added.…”
Section: Animalsmentioning
confidence: 99%